Research progress of neoantigen-based dendritic cell vaccines in pancreatic cancer - Zhang, Xin; Xu, Zheng; Dai, Xiangpeng; Zhang, Xiaoling; Wang, Xueju (Frontiers in Immunology, 2023)
The mutation of the crucial genes such as tumor suppressors or oncogenes plays an important role in the initiation and development of tumors. The non-synonymous mutations in the tumor cell genome will produce non-autologous proteins (neoantigen) to activate the immune system by activating CD4+ and CD8+ T cells. Neoantigen-based peptide vaccines have exhibited exciting therapeutic effects in treating various cancers alone or in combination with other therapeutic strategies. Furthermore, antigen-loaded DC vaccines are more powerful in inducing stronger immune responses than vaccines generated by antigens and adjuvants. Therefore, neoantigen-based dendritic cell (DC) vaccines could achieve promising effects in combating some malignant tumors. In this review, we summarized and discussed the recent research progresses of the neoantigen, neoantigen-based vaccines, and DC-based vaccine in pancreatic cancers (PCs). The combination of the neoantigen and DC-based vaccine in PC was also highlighted. Therefore, our work will provide more detailed evidence and novel opinions to promote the development of a personalized neoantigen-based DC vaccine for PC.